Comparative Genomic Analysis of the Interferon/Interleukin-10 Receptor Gene Cluster - Reboul, Jérôme; Gardiner, Katheleen; Monneron, Danièle; Uzé, Gilles; Lutfalla, Georges (Genome Research, 1999)
Interferons and interleukin-10 are involved in key aspects of the host defence mechanisms. Human chromosome 21 harbors the interferon/interleukin-10 receptor gene cluster linked to theGART gene. This cluster includes both components of the interferon α/β-receptor (IFNAR1 and IFNAR2) and the second components of the interferon γ-receptor (IFNGR2) and of the IL-10 receptor (IL10R2). We report here the complete gene content of this GART–cytokine receptor gene cluster and the use of comparative genomic analysis to identify chicken IFNAR1, IFNAR2, andIL10R2. We show that the large-scale structure of this locus is conserved in human and chicken but not in the pufferfish Fugu rubripes. This establishes that the receptor components of these host defense mechanisms were fixed in an ancestor of the amniotes. The extraordinary diversification of the interferon ligand family during the evolution of birds and mammals has therefore occured in the context of a fixed receptor structure.[The sequence data described in this paper have been submitted to GenBank under accession nos.AF039904, AF039905, AF039906, AF039907, AF045606, AF082664, AF082665,AF082666, AF082667, and AF083221.]